Moving on from Scaling Up: Further Progress in Developing Social Impact Measurement in the Third Sector. (2nd January 2017) - Dey, Colin; Gibbon, Jane
ABSTRACT: In 2011, we published an article in SEAJ [Gibbon, J., and C. Dey. 2011. "Developments in Social Impact Measurement in the Third Sector: Scaling Up or Dumbing Down?" Social and Environmental Accountability Journal 31 (1): 63–72] that explored various issues surrounding the measurement of social impact in Third Sector Organisations. In the little over five years since it was published, we have been surprised to discover that our article has emerged as one of SEAJ 's most cited (and downloaded) publications. This prompted us to take a closer look at where our paper was being cited and obtain further insight as to why and how the paper has been used across a variety of fields, within both theoretical and empirical studies, by both academics and practitioners. Relevant to both researchers and practitioners, our review provides a useful snapshot that brings together a broad literature to explore how and where social impact measurement for social enterprise and values-based organisations is developing.